2016
DOI: 10.15326/jcopdf.3.4.2016.0136
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Patients With COPD at High Risk of Readmission

Abstract: Background: Readmission within 30 days of a COPD hospitalization is a common measure of performance for COPD care. However, most studies of COPD readmission risk have been constrained to a single data source, private payer claims, or Medicare claims data, making it difficult to generalize results from these studies to other populations. The purpose of this study was to examine the risk for readmission within 30 days from time of discharge in patients with COPD using the Healthcare Cost and Utilization Project … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
54
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(60 citation statements)
references
References 22 publications
5
54
1
Order By: Relevance
“…30 Second, by using SID and Elixhauser comorbidities variables, previous studies have shown that among comorbid COPD patients-including congestive heart failure, lung cancer, weight loss, deficiency anemias, hypertension, diabetes, hypothyroidism, lymphoma, alcohol abuse, obesity, chronic kidney disease and obstructive sleep apnea-the risk of 30-day all-cause or COPD-related readmission did not differ from patients without comorbidities. 13,16,17 One possible explanation is that a primary COPD diagnosis among comorbid patients could motivate them to modify their health behaviors by trying to increase physical activities and monitoring their diet. 38 Furthermore, COPD patients with comorbidities often consulted family physicians more, which may in turn have resulted in better health outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…30 Second, by using SID and Elixhauser comorbidities variables, previous studies have shown that among comorbid COPD patients-including congestive heart failure, lung cancer, weight loss, deficiency anemias, hypertension, diabetes, hypothyroidism, lymphoma, alcohol abuse, obesity, chronic kidney disease and obstructive sleep apnea-the risk of 30-day all-cause or COPD-related readmission did not differ from patients without comorbidities. 13,16,17 One possible explanation is that a primary COPD diagnosis among comorbid patients could motivate them to modify their health behaviors by trying to increase physical activities and monitoring their diet. 38 Furthermore, COPD patients with comorbidities often consulted family physicians more, which may in turn have resulted in better health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Individual-level factors, obtained from HCUP SID, included gender, race, age and types of primary insurance payer. 7,16,31 Hospital-level factors included number of beds; teaching hospital; residency training approval hospital; hospital location and Medicare Accountable Care Organization (ACO) types: Pioneer or Medicare Shared Savings Program (MSSP); 32,33 information collected from the AHA Annual Survey and the level of implementation of health information technology, collected from the Health Information and Management System Society. Geographic level factors consisted of median household income (reported by quartiles of the patient's ZIP code and acquired from AHRF), Herfindahl-Hirschman index (defined as the sum of square market shares of inpatient days measured in a county, 34 which was obtained from AHA survey), and state-fixed effects.…”
Section: Covariatesmentioning
confidence: 99%
See 2 more Smart Citations
“…38 Reasons for low adherence observed here are unclear. The prevalence of obesity and use of Medicaid (a program helping to pay health care costs for patients with limited income) were high in this population compared with COPD populations in other studies [39][40][41] and the general population (44.9% of participants were obese vs. an estimated prevalence of 39.8% among U.S. adults in 2015e2016, 42 and 47.1% of participants had Medicaid coverage vs. approximately 19.4% of the U.S. population in 2016). 43 These observations might suggest a Table 2 Distributions of participants according to the GOLD 2016 classifications of airflow limitation, mMRC and CAT scores, and exacerbation history (percentages of evaluable sample unless otherwise stated) 25 682) and out of the subgroup of participants with available spirometry data (n ¼ 251).…”
Section: Discussionmentioning
confidence: 75%